A Review of Database Attacks - Bassani, Matteo; Bagui, Sikha (Transactions on Engineering and Computing Sciences, 2024)
In today’s world, where organizations heavily rely on databases to store and access critical information, database security is a major concern. This paper provides an overview of recent trends and popular threats in database security, as well as an organized literature review of database attacks and related security methods. The primary objectives of this review are to analyze the current state of database attacks, highlight effective defense techniques, and identify research gaps and future directions. The paper categorizes the reviewed literature into various sections, including general database attacks, SQL Injection attacks, Cross-Site Scripting (XSS) attacks, Denial of Service (DoS) attacks, mixed attacks, other types of attacks, and concludes with database encryption techniques. By examining the merits and demerits of existing approaches, this review aims to contribute to a better understanding of database attacks and their related countermeasures. Finally, the findings of this paper can help researchers improve their understanding of the topic and make progress in the study of techniques to address threats to data availability, confidentiality, and integrity.